The macroeconomic effects of a pandemic in Europe : a model-based assessment - Jonung, Lars.; Roger, Werner; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
The spread of avian flu has led to fears of a worldwide pandemic. This fear is based on the view that the H5N1 bird flu virus may mutate into a disease that will easily and rapidly spread from human to human and that no effective vaccine will exist to counter such an outbreak. In response to this possible health catastrophe, several reports on the economic consequences of a major epidemic have been produced recently. So far there has been no study of the potential consequences of a pandemic on the economies of the EU Member States. The purpose of this report is to fill this gap by estimating the likely macroeconomic effects of a pandemic using a quarterly macro-model constructed and calibrated for the EU-25 as one single economic entity. The use of such a macro-model has several advantages....This report is organized as follows. First, we briefly consider some studies on the economic effects of large epidemics, focusing on the assumptions concerning the characteristics of a future pandemic, as these assumptions are extremely crucial for the results obtained. Second, we perform a number of simulations using a macro-model developed within DG ECFIN, the QUEST model, to study various pandemic scenarios; first a baseline scenario, then the same scenario modified by the introduction of new assumptions. Here, we compare our results with those obtained for the United States. Third, we examine the impact on tourism and trade, two sectors of the European economy that are assumed to be severely hit.
Economic Papers